measuring viscoelastic properties of Red Blood Cell using optical tweezers - S N Seyed Reihani; A Azadbakht; E Mirzahossein; M Mottaghian; M Babaei (Iranian Journal of Physics Research, 2019)
Efforts have been made to study the behavior of complex materials in micrometer dimensions with various techniques. One of these methods is the use of optical tweezers for biophysical applications. Red blood cells, as the most abundant blood-forming cells, play an important role in the life of living organisms, and their unique mechanical properties are important. In this report, the study of soft materials is done using light tweezers. This work investigates micrometer particle movements in the optical trap and also, when they are connected to a red blood cell. The tweezers allow the Newtonian fluid viscosity, such as water and glycerin, to measure the mechanical properties of viscoelastic materials, such as red blood cells.